The Binding Power of the Bapalas Tradition to Solve Dayak Citizens' Disputes in West Kotawaringin District - Sukti, Surya; Khair, Abdul; Mualimin, Mualimin; Arifin, Imam S (Jurnal Ilmiah Al-Syir'ah, 2023)
The background to this research is that if a dispute occurs between Dayak people, especially those living in West Kotawaringin Regency, some choose to resolve the problem peacefully through the Bapalas custom. A traditional Mantir leads the Bapalas tradition, and the decision of this traditional Mantir is firm because it follows the elements of article 1320 BW. In article 1320 BW, there are four conditions for an agreement's validity: agreement, skill, a sure thing, and a lawful cause. So, if it is related to article 1320 BW, problems that occur in society can be resolved with an agreement. This tradition of Bapalas in the people of West Kotawaringin Regency follows Islamic law, known as Islah or peaceful problem-solving in Islam. This research analyzes the legal certainty aspect of traditional Mantir decisions in Bapalas. This research method is a field research method, and the approach is qualitative. What is very interesting is that this traditional Mantir can solve various civil and criminal problems. For criminal cases, several cases, such as fights and abuse, can also be resolved using the Bapalas method. The basis of this Dayak traditional institution is Central Kalimantan Province Regional Regulation Number 16 of 2008 concerning Dayak Traditional Institutions in Central Kalimantan.